Ayurvedic Management of Otomycosis - A Case Study - Magi, Sujata; Hiremath, Veerayya R; Shashikala , D K; Gururaj , N; Raju , S N (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Otomycosis is a type of otitis externa occurring due to fungal infection characterized by intense itching, pain in the ear, watery discharge and ear blockage. It is frequently seen in hot and humid climate of tropical and subtropical countries. In general population, the prevalence of otomycosis is 5.2% all over world and in India 9%. Further 5-25% otitis externa is due to otomycosis. The 90% of fungal infection involves Aspergillus Niger and rest Candida Albicans species. Treatment includes Aural Toileting, administration of antifungal agents or antibiotic steroid ear drops. These drugs have common side effects like burning sensation, irritation, swelling of the ear. Based on signs and symptoms it can be correlated to karnakandu. Karnakandu is caused by vitiation of either Kapha dosha alone or combined with Vata dosha and it is characterized by itching sensation and inflammation in the ear canal. Treatment includes Nadisveda, Vamana, Murdhavirechana, Dhoomapana and Sarva kapha nashaka chikitsa. Materials And Methods: A 45 year male patient visited our OPD with complaining of itching, aural blockage and pain in the ear since 15 days. He was treated with karnapramarjana followed by antifungal arka ear drops 2 drops TID and Tablet Nimbadi Guggulu 1 TID for 7 days. Conclusion: Patient got complete relief form all signs and symptoms. Thus it can be concluded that, Antifungal Arka Ear drops can be advised for successful treatment in patients of Karnakandu (Otomycosis) as it is cost effective, ease of administration and given better efficacy in treatment.